PENGKAJIAN HADIS DI ERA MODERN (KONTRIBUSI DAN KARYA INTELEKTUAL PROF. DR. ABDUL MUHDI) - Nur, Imamul Authon; Harahap, Radinal Mukhtar (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2025)
AbstractThe aim of this study is to investigate the contribution of Prof. Dr. Abdul Muhdi to the field of hadith. The names mentioned can be classified as modern hadith figures whose thoughts and academic achievements are documented and serve as reference for hadith scholars. In this study, several of his works (library research) are discussed, namely Ṭuruq Takhrīj Ḥadīṡ Rasūli Allah Sallā Allahu 'Alaihi Wa Sallam, Ṭuruq Takhrīj Aqwāl aṣ-Ṣaḥābah wa at-Tābi'īn wa at-Takhrīj bi al-Kumbiyutar, al-Madkhal Ilā as-Sunnah an-Nabaiwyyah, as-Sunnah an-Nabawiyyah: Makānatuhā wa 'Awāmilu Baqāiha wa Tadwīnuhā, Musnad Ibn Ja'ad: Taḥqīq wa Dirāsah, Ilmu al-Jarḥ wa at - Ta'dīl: Qawā'iduḥu wa Aimmatuḥu, Daf'u asy-Syubhat 'An as-Sunnah an-Nabawiyyah, and Aḥādīṡu Mu'jizāt ar-Rasūl Sallā Allahu 'Alaihi wa Sallam Allati Ẓaharat fi Zamāninā. Based on the findings of this study, it is known that the contribution of Prof. Dr. Abd Muhdi in the field of hadith is quite extensive, including the study of the Tahkik Kitab, the collection of hadith and syrah, as well as in the field of jarh and ta'dil science. Prof. Dr. Abd Muhdi also contributed to the methodology of hadith research and establishing the rules of takhrij science. He also actively refuted the accusations against the hadith and their narrators. Therefore, this article can serve as an introduction to further research into his biography and thought, within the context of the combination of classical and contemporary hadith studies.AbstrakPenelitian ini bertujuan untuk mengetahui kontribusi Prof. Dr. Abdul Muhdi dalam bidang hadis. Nama yang disebutkan dapat dikategorikan sebagai tokoh hadis era modern yang, baik pemikiran maupun kinerja akademiknya, telah dibukukan dan menjadi rujukan para pengkaji hadis. Penelitian ini akan meninjau beberapa karyanya (library research) yaitu Ṭuruq Takhrīj Ḥadīṡ Rasūli Allah Sallā Allahu ‘Alaihi Wa Sallam, Ṭuruq Takhrīj Aqwāl aṣ-Ṣaḥābah wa at-Tābi’īn wa at- Takhrīj bi al-Kumbiyutar, al-Madkhal Ilā as-Sunnah an-Nabaiwyyah, as-Sunnah an-Nabawiyyah: Makānatuhā wa ‘Awāmilu Baqāiha wa Tadwīnuhā, Musnad Ibnu Ja’ad: Taḥqīq wa Dirāsah, Ilmu al-Jarḥ wa at—Ta’dīl: Qawā’iduḥu wa Aimmatuḥu, Daf’u asy-Syubhat ‘An as-Sunnah an-Nabawiyyah dan Aḥādīṡu Mu’jizāt ar-Rasūl Sallā Allahu ‘Alaihi Wa Sallam Allati Ẓaharat fi Zamāninā. Berdasarkan hasil penelitian ini, diketahui bahwa kontribusi Prof. Dr. Abd Muhdi dalam bidang Hadis cukup banyak meliputi kajian tahkik kitab, penghimpunan hadis dan syarah, serta dalam ilmu jarh dan ta’dil. Prof. Dr. Abd Muhdi juga berkontribusi dalam metodologi penelitian hadis dan dalam meletakkan kaidah-kaidah ilmu takhrij. Dirinya juga aktif membantah tuduhan-tuduhan seputar hadis dan perawinya. Dengan begitu, artikel ini dapat menjadi pengantar atas penelitian selanjutnya, baik biografi maupun pemikirannya, dalam kerangka menghubungan kajian hadis klasik dan kontemporer.